Product availability from delivery aspect – evidence from retailers in selected Western Balkan countries - Grubor, Aleksandar; Milicevic, Nikola M (Industrija, 2016)
Bearing in mind that it represents one of the main preconditions of sales, product availability is the key task of retail companies and their delivery systems. This paper analyses its levels from the aspect of centralized and DSD systems. The research is conducted in Serbia, Bosnia and Herzegovina and Montenegro, including 84 stores and more than 70 FMCG products per each store. Thereby, the comparisons in product availability levels between alternative delivery systems are carried out within different trading formats and within different product categories. Unlike the results of similar studies and ongoing changes on retail markets, this research shows that at retailers in these Western Balkan countries, availability levels are higher in the case of DSD system.
Keywords: Retail formats; Distribution center; Delivery; Retail; Product availability